Confirmatory Factor Analysis of the Universiti Sains Malaysia Emotional Quotient Inventory Among Medical Students in Malaysia - Arifin, Wan Nor; Bahri Yusoff, Muhamad Saiful (SAGE Publications, 2016)
The Universiti Sains Malaysia Emotional Quotient Inventory (USMEQ-i) is a Malay-language emotional intelligence (EI) inventory that was based on a mixed-model approach of EI. It was specifically developed and validated for use among medical course applicants. However, evidence to support its use among medical students is inadequate. This study aims to provide further construct validity evidence for the USMEQ-i among medical students through confirmatory factor analysis (CFA). A cross-sectional study was carried out on a sample of 479 medical students in Universiti Sains Malaysia (USM). After a preliminary analysis, data from only 317 respondents were found suitable for inclusion in CFA. CFA was performed using the maximum likelihood estimation method with bootstrapping due to the nonnormality of items at the multivariate level. The results of the analysis support the two-factor model of the EI component and the one-factor model of the faking component. However, the USMEQ-i should be administered with caution until further cross-validation studies are conducted among students in other medical schools in Malaysia.